Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan Perusahaan Pada PT. Industri Jamu dan Farmasi Sido Muncul Tbk. Periode 2021-2023 - Maheruddin, M Habib; Sepfianszah, Leny; Pancawati, Lilin; Najib, MTA (Bata Ilyas Journal of Accounting, 2024)
This research discusses financial ratios which are used to measure the company's financial performance at PT. Sido Muncul Herbal Medicine and Pharmaceutical Industry Tbk. 2021-2023 period. In 2021-2022, PT Industri Jamu dan Farmasi Sido Muncul Tbk's revenue/profits will decrease, even though it can be seen that this company looks quite large. Therefore, researchers want to analyze the financial reports of PT Industri Jamu dan Farmasi Sido Muncul Tbk whether in 2023 they will continue to decline or experience an increase in income/profits. The novelty in this research is in the margin data for each ratio used. The method used is a quantitative method that uses financial ratio analysis and the information in this research was obtained from the financial reports of the company PT. Sido Muncul Herbal Medicine and Pharmaceutical Industry Tbk. 2021 to 2023. Results of calculating financial ratios on PT's financial statements. Sidomuncul in 2021-2023 uses liquidity, solvency, activity and profitability ratios where the company can still be said to be in good condition even though there is a decrease in the ratio calculation from 2021 to 2023